Statistical methods : for agricultural and biological sciences - Amdekar, S. J. (Oxford, U.K. : Alpha Science International Ltd., 2014)
Statistical Methods for Agricultural and Biological Sciences introduces basic statistical concepts as are required for understanding of applications of statistical techniques. There is simplicity in presentation involving no mathematical derivations. All the topics are introduced as well as explained with live examples for the reader to feel comfortable with topics like mean, variance, probability, probability distributions, hypothesis testing, correlation and regression analysis, experimental designs and analysis of factorial experiments which are useful in every scientific investigation that involve data.
Probability and probability distributions -- Sampling distributions -- Testing of hypothesis -- Analysis of variance -- Correlation and regression analysis -- Design of experiment -- Factorial experiment.
Keywords: Agriculture -- Statistical methods